Hemorrhage from Extra-Antral Gastric Antral Vascular Ectasia in a Patient with Duodenal Heterotopic Gastric Mucosa - John Gubatan; Nathan Raines; Hasan Khosravi; Tracy L. Challies; Tyler M. Berzin (Case Reports in Gastrointestinal Medicine)
Gastric antral vascular ectasias (GAVE) have been increasingly recognized as an uncommon cause of chronic gastrointestinal bleeding and anemia, although their underlying pathogenesis is not completely well understood. Heterotopic gastric mucosa (HGM) has been reported to occur at various sites along the gastrointestinal tract and although relatively common, it is often asymptomatic. We report a case of a 60-year-old woman with a prior history of GAVE who developed melena and symptomatic anemia during her hospitalization following cardiac catheterization. Initial EGD demonstrated nonbleeding antral GAVE and a newly discovered duodenal mass. Duodenal mass biopsies were ultimately notable for HGM along with histologic features of extra-antral GAVE. The patient required blood transfusions and consequently had a small bowel endoscopy notable for fresh blood in the proximal small bowel. The patient underwent a small bowel push enteroscopy which demonstrated active bleeding of the duodenal mass and overlying oozing GAVE, which was cauterized with Argon-Plasma Coagulation with adequate hemostasis. We present for the first time a novel association between GAVE and HGM. Our case illustrates that extra-antral GAVE may occur with HGM in the duodenum. We explore potential mechanisms by which HGM may be involved in the pathogenesis of GAVE.